Service Quality Gap and its Impact on the Performance of Indian Health Insurance Companies (Global Journal of Management and Business Research, 2018)
This manuscript presents mixed research paradigm based empirical assessment of the Service Quality Gap (SQG) in Indian Health Insurance Companies (HICs) and its impact on the firm's performance. This study applied SERVQUAL model with seven dimensions, Reliability, Tangibles, Responsiveness, Empathy, Assurance, Credibility, and Competency to perform SQG assessment. Being empirical study responses from HIC customers belonging to the different demographic constructs have been examined for consumer's expectation and perceived service quality. This empirical study revealed that there is negative SQG (-1.53) in reliability that motivates HICs to focus on facilitating promised services to retain customer's confidence. The SQG values in other dimensions like tangibility (1.7), assurance (1.61), responsiveness (1.52), empathy (1.56), credibility (1.97), and competency (1.44) too signify quality gap in current services. It has been found that customers feel that HICs are emphasizing on tangibility and credibility dimensions to meet fundamental need of health insurance. SQGs obtained indicate towards more productive and augmented quality enriched provision like cash withdraw machinery such as ATM, claim provision through ATM, notification through mails, electronic CRM (e-CRM) facilities. It also reveals that HICs must be willing to help customers and must answer them promptly with effective communication and solution. Empathy dimension reflects maximum quality gap that demands HICs to let consumer access major facilities to promote satisfaction and productivity.
Keywords: indian health insurance companies; service quality gap; firm performance